Mathquest aljabar: Inovasi media pembelajaran interaktif berbasis discovery learning berbantuan canva - Silvia Putri Tsani; Wahyu Hidayat; Eva Dwi Minarti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Mathematical critical thinking ability among junior high school students remains low, particularly in learning algebraic expressions. This issue is partly caused by limited opportunities for students to explore concepts independently. This study employed the Research and Development method using the ADDIE model to develop, evaluate, and examine the effectiveness of a Canva-based interactive learning tool integrated with Discovery Learning. The research was conducted at a junior high school in Cimahi through one-to-one, small-group, field-trial, and implementation stages. Data were collected through written tests, validation sheets completed by three experts, student interviews, and student responsse questionnaires. The results showed that the developed Canva-based interactive learning tool was highly valid according to expert assessments. Furthermore, the field trial demonstrated that the tool was highly practical and effective in improving students’ mathematical critical thinking skills in algebraic expressions. This study provides an alternative digital learning tool that integrates Canva and Discovery Learning to facilitate the learning of abstract mathematical concepts.